Comments on the cross-relaxation effect between adsorbed 3He and PrF3 nanoparticles - Alakshin, E.M.; Tagirov, M.S.; Safiullin, K.R.; Safin, T.R.; Rodionov, A.A.; Orlinskii, S.B.; Klochkov, A.V.; Gazizulina, A.M.; Gazizulin, R.R.; Zakharov, M.Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The spin kinetics data of 3He in contact with PrF3 and LaF3 nanosized powders are reported. All experimentshave been carried out by pulse NMR methods at temperature 1.5 K. The analysis of obtained data testifies in favor of cross-relaxation presence in the nuclear spin–lattice relaxation data, which takes place between 3He and 141Pr nuclei.